Effect of ketamine on transcranial Doppler Gosling pulsatility index in children undergoing procedural sedation: A pilot study - Christopher T. Stem; Sriram Ramgopal; Robert W. Hickey; Mioara D. Manole; Jeffrey R. Balzer (Journal of the American College of Emergency Physicians Open)
Abstract Objectives There has been controversy over whether ketamine affects intracranial pressure (ICP) in children. Transcranial Doppler ultrasound (TCD) is a validated technique used to assess ICP changes noninvasively. Gosling pulsatility index (PI) directly correlates with ICP changes. The objective of this study was to quantify PI changes as a surrogate marker for ICP changes in previously healthy children receiving intravenous ketamine for procedural sedation. Methods We performed a prospective, observational study of patients 5–18 years old who underwent sedation with intravenous ketamine as monotherapy. ICP changes were assessed by surrogate PI at baseline, immediately after ketamine administration, and every 5 minutes until completion of the procedure. The primary outcome measure was PI change after ketamine administration compared to baseline (denoted ΔPI). Results We enrolled 15 participants. Mean age was 9.9 ± 3.4 years. Most participants underwent sedation for fracture reduction (87%). Mean initial ketamine dose was 1.4 ± 0.3 mg/kg. PI decreased at all time points after ketamine administration. Mean ΔPI at sedation onset was –0.23 (95% confidence interval [CI] = –0.30 to –0.15), at 5 minutes was –0.23 (95% CI = –0.28 to –0.18), at 10 minutes was –0.14 (95% CI = –0.21 to –0.08), at 15 minutes was –0.18 (95% CI = –0.25 to –0.12), and at 20 minutes was –0.19 (95% CI = –0.26 to –0.12). Using a clinically relevant threshold of ΔPI set at +1 (+8 cm H2O), no elevation in ICP, based on the PI surrogate marker, was demonstrated with 95% confidence at all time points after ketamine administration. Conclusions Ketamine did not significantly increase PI, which was used as a surrogate marker for ICP in this sample of previously healthy children. This pilot study demonstrates a model for evaluating ICP changes noninvasively in the emergency department.